Design of a prototype generator based on piezoelectric power generation for vibration energy harvesting - Nyamayoka, Lumbumba Taty-Etienne; Adewumi, Gloria Adedayo; Inambao, Freddie Liswaniso (Journal of Energy in Southern Africa, 2017)
The concept of harvesting energy in the ambient environment arouses great interest because of the demand for wireless sensing devices and low-power electronics without external power supply. Harvesting energy by vibration with piezoelectric materials can be used to convert mechanical energy into electrical energy that can be stored and used to power other devices. This conversion of vibrations (mechanical energy) to electrical energy using piezoelectric materials is an exciting and rapidly developing area of research with a widening range of applications constantly materialising. In this context, the goal of this paper is to develop a comprehensive prototype generator that can harvest vibration energy and convert it to electrical energy by providing the output power for optimisation and its performance. Two setups of prototype are used: a cantilever beam with tip mass at the end, and a cantilever beam without tip mass at the end. Data from the experiment is compared and analysed using MatLab. The results show that the power output of the prototype with the tip mass is greater than the power output without the tip mass. The experimental results led to a power optimisation from that prototype by different characteristic of piezoelectric ceramic plate.